Insulin resistance is associated with verbal memory impairment in bipolar disorders - Salvi, Virginio; Di Salvo, Gabriele; Korčáková, Jana; Torriero, Sara; Aragno, Elena; Kolenič, Marian; Ungrmanová, Martina; Maina, Giuseppe; Mencacci, Claudio; Hajek, Tomas (Journal of affective disorders, 2020)
BACKGROUND: Cognitive impairment contributes to deterioration in social, family and work functioning in Bipolar Disorder (BD). Cognitive deficits are present not only during, but also outside of mood episodes. Insulin resistance (IR) impairs cognitive functioning and is frequent in participants with BD. Thus, we hypothesized that IR might contribute to cognitive deficits in remitted BD participants. METHODS: We acquired biochemical (fasting insulin, glucose, lipids) cognitive (California Verbal Learning Test, Digit Span) measures from 100 euthymic participants with BD type I or II. IR was diagnosed using HOMA-IR. RESULTS: BD participants with IR displayed worse composite verbal memory score (-0.38 vs 0.17; F(1, 8.23)=17.90; p = 0.003), while composite working memory scores were comparable in patients with or without IR (-0.20 vs 0.07; F(1, 6.05)=1.64; p = 0.25). Insulin resistance remained significantly associated with composite verbal memory scores (F(1, 47.99)=9.82, p = 0.003) even when we controlled for levels of lipids. The association between IR and verbal memory was not confounded by exposure to antipsychotics, which were not associated with worse cognitive performance (F(1, 2.07)=5.95, p = 0.13). LIMITATIONS: The main limitation is the cross-sectional design, which does not allow us to rule out reverse causation. CONCLUSIONS: We demonstrated that among remitted BD participants without diabetes mellitus, IR was significantly associated with verbal memory performance, even when we controlled for other relevant metabolic or treatment variables. These findings raise the possibility that early detection and treatment of IR, which is reversible, could possibly improve cognitive functioning in at least some BD participants.
Keywords: Bipolar disorder; Cognitive function; průřezové studie; Insulin Resistance; Bipolar Disorder; Cross-Sectional Studies; Neuropsychological Tests; neuropsychologické testy; Verbal; inzulinová rezistence; lidé; poruchy paměti; Insulin resistance; Memory Disorders; Humans; bipolární porucha; Memory; paměť